Satisfaction and use of the didactic simulator for learning the nursing process: an observational study - Alberto Cruz-Barrientos; Eva Manuela Cotobal-Calvo; Ana María Sainz-Otero; José Manuel De-; Daniel Román-Sánchez; Inés Carmona-Barrientos (BMC, 2024)
Abstract Introduction The implementation of Information and Communication Technology (ICT) in daily healthcare practice has become standardized. In relation to education within the nursing degree, ICTs make it possible to carry out practical immersion training from the" classroom or from any other place with an Internet connection, as evidenced by circumstances that have occurred in recent years, such as the pandemic caused by COVID-19. Objective Design and assess a didactic simulation program for the training of the nursing process that promotes learning in the nursing care Methodology The methodological approach is quantitative and it is a descriptive cross-sectional study. The sampling method used was non-probabilistic by convenience. Results When observing the comparison of the averages of student satisfaction with respect to the didactic simulator, it is worth mentioning that all the items are above 2.80 on a score in which "0" is the minimum value and "5" the maximum value. The results of the use of the computer tool by the students, we highlight as significant data that all the items present an average equal to or lower than 3.04 out of 7, where "1" corresponds to a lot of use and "7" to little use. Conclusion The implication of ICT in the teaching-learning process among Nursing Degree students, it is considered optimal. when analyzing the answers obtained in the items that refer to a higher ease in the execution of development of Care plans, a fundamental work in Nursing performance.